A monomeric [Zr(CO3)4]4− complex in an ammonium zirconium carbonate aqueous solution studied by extended X-ray absorption fine structure, Raman and nuclear magnetic resonance spectroscopy. Issue 2 (11th November 2014) - Takasaki, Fumiyuki; Fujiwara, Kazuhiko; Nakajima, Yasushi; Nishikawa, Taku; Masu, Hyuma; Imanari, Mamoru; Hidaka, Yuki; Ogawa, Nobuaki
Abstract : A monomeric complex, [Zr(CO3 )4 ] 4−, is able to exist under certain conditions. Abstract : The speciation of zirconium complexes in ammonium zirconium carbonate (AZC) solutions should be further studied in order to develop high-performance AZC complexes for use in elaborate industrial materials. Thus, the speciation and the structure of various zirconium species in ammonium zirconium carbonate solutions were investigated over a wide range of total carbonate and ammonium concentrations. By employing extended X-ray absorption fine structure analysis, and Raman and 13 C NMR spectroscopy, it was found that four carbonate ions coordinate bidentately to the zirconium ion. In addition, the exact concentration ranges of carbonate and ammonium in AZC necessary to generate the monomeric zirconium carbonate complex [Zr(CO3 )4 ] 4− were determined.